The demographic dividend : a new perspective on the economic consequences of population change - Bloom, David E. (David Elliot), 1955- (Online Rand research documents., 2003)
There is a long-standing debate on how population growth affects national economies. A new report from Population Matters examines the history of this debate and synthesizes current research on the topic. The authors, led by Harvard economist David Bloom, conclude that population age structure, more than size or growth per se, affects economic development, and that reducing high fertility can create opportunities for economic growth if the right kinds of educational, health, and labor-market policies are in place. The report also examines specific regions of the world and how their differing policy environments have affected the relationship between population change and economic development.